ANALYSIS OF FACTORS INFLUENCING CONSUMERS' PURCHASING DECISIONS AT DINAR PHOTOCOPY IN KUTAGANDOK KARAWANG - Hendriawan, Abdulrahman; Ramadhan, Fajar (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Photocopy businesses continue to survive amid digital technology advancements. However, intense competition and changes in consumer behavior present challenges for business owners. The fluctuations in customer numbers and revenue at Dinar Photocopy throughout 2023 indicate the presence of specific factors influencing consumer purchasing decisions. Therefore, this study aims to analyze the key factors affecting purchasing decisions at Dinar Photocopy to help business owners develop more effective marketing strategies. The objective of this research is to identify the factors influencing purchasing decisions at Dinar Photocopy. Research methodology is essentially a scientific approach to obtaining data for specific purposes and applications. This study employs a quantitative descriptive method. The findings reveal that perception, convenience, product variety, and service quality each have a positive and significant influence on purchasing decisions, while ease of access has a positive but insignificant effect. Furthermore, when considered simultaneously, the factors of perception, ease of access, convenience, product variety, and service quality collectively have a positive and significant impact on purchasing decisions.